2020
DOI: 10.3390/jcm9093056
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Fetal Thyroid Levels at Delivery among Appalachian Infants

Abstract: Thyroid disorders are a frequently encountered issue during pregnancy and a cause of maternal and fetal morbidity. In regions like Appalachia that are particularly susceptible to health disparities, descriptive studies are needed to assist in identifying pathologic derangements. We sought to characterize fetal thyroid hormone levels at delivery and investigate whether or not maternal demographic characteristics affect the prevalence of neonatal thyroid disease. A cross-sectional analysis was conducted on 130 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 26 publications
(19 reference statements)
0
0
1
Order By: Relevance
“…The mean cord blood Free T4 in our study was 0.61 ng/dL, while other studies reported different results (3,37,38). We observed that the mean cord blood Free T4 was signi cantly higher in multigravida newborns than primigravida newborns.…”
Section: Discussioncontrasting
confidence: 79%
“…The mean cord blood Free T4 in our study was 0.61 ng/dL, while other studies reported different results (3,37,38). We observed that the mean cord blood Free T4 was signi cantly higher in multigravida newborns than primigravida newborns.…”
Section: Discussioncontrasting
confidence: 79%